Genetic algorithm for designation of safe ship trajectory - Mohamed-Seghir, M. (Scientific Journal of Gdynia Maritime University, 2017)
The article presents a multi-stage decision-making process in the fuzzyenvironment, using a method based on genetic algorithm. Whose structure has beendeveloped specifically for the problem of determining the optimal safe ship trajectory incollision situations, taking into account the provisions of the international law of the sea routewith the International Maritime Organization convention on the International Regulations forPreventing Collisions at Sea (COLREGs).